PENERAPAN BUDAYA RELIGIUS DI SEKOLAH MENENGAH ATAS NEGERI 7 BANDA ACEH - QURRATA AKYUNI (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
Religious culture has a very important role that must be developed in schools. Because school are one place to transform values, with Islamic culture it will be easier for schools to transfer values ​​to students. Transfer of these values ​​is not enough just for learning to classroom, but also carried out outside of learning so that the value ​​is really attached to students and form characters. This is what makes the application of religious culture at the 7th State Senior High School Banda Aceh very necessary. Religious culture in application can be seen from various forms, namely the values ​​adopted in schools, daily practices and cultural symbols. This study aims to describe the forms of Islamic culture in State Senior High School 7 Banda Aceh. The type of research used is descriptive qualitative. The results showed that the application of religious culture at SMAN 7 Banda Aceh has high aspirations in realizing religious culture in schools, this can be seen from the vision and mission of the school prioritizing in realizing Islamic symbols in schools. Religious culture in schools can also be seen by the existence of planned and programmed Islamic activities in schools carried out by the school.